(untitled) (Ukrainian Journal of Ophthalmology, 2025)
Background: Exophoria may be caused by congenital or acquired anomalies in orbital structure, ocular structure, extraocular muscle attachment and/or extraocular muscle location. Some researchers believe that the presence of stereopsis after treatment for strabismus indicates that a stable treatment outcome has been achieved and binocular vision regained. The state of stereopsis is believed to be an efficacy endpoint in the evaluation of strabismus surgery. Purpose: To assess stereopsis before and after surgery for constant versus intermittent exotropia. Material and Methods: Fifty-nine patients with constant or intermittent exotropia, aged 10 to 21 years, were included in the study. Of these, 33 (group 1) had constant exotropia and 26 (group 2), intermittent exotropia. They underwent surgery on one or both eyes. Visual acuity assessment, refractometry, and biomicroscopy were performed, near and distance angles of deviation were measured by Hirschberg’s test and prism cover test, the color test was used to determine the type of binocular vision, and synoptophore, to examine fusion both before and after treatment. Stereoacuity thresholds were assessed with Lang-Stereotest II and Titmus Stereo Fly (circles and animals) tests at daylight at a viewing distance of 30 cm and a Huvitz CCP3100 Chart Projector was used to assess whether stereopsis was present at a 5-m distance. Results: After treatment, the magnitude of exotropia decreased in all patients, and the mean angle of deviation at near was 3.5±1.4 degrees, and at distance, 3.9±1.9 degrees. In addition, 70% of patients regained binocular vision. At baseline, neither patient in group 1 and only three patients in group 2 exhibited distance stereopsis. After treatment for strabismus, 11 patients in group 1 exhibited near stereopsis, and stereoacuity threshold as assessed by the Titmus Stereo Fly (circles and animals) test was 200-400 arc sec in 24.4% of patients of this group. In addition, in 80.8% of patients of group 2, the stereoacuity threshold was 1500 arc sec, and the stereoacuity normalized and was 200 arc sec as assessed by the circles subtest. That is, after surgery, stereoacuity thresholds decreased substantially, especially in group 2. Conclusion: After surgery, in 70-80% of cases, stereoacuity increased (stereoacuity thresholds decreased), indicating that the surgical treatment was effective and binocular functions were regained. Our preliminary results suppose that a preoperative near stereoacuity of 200 arc sec will be a favorable factor for improvement in binocular functions and stable orthotropia after surgery for intermittent exotropia.